Optimization of fermentation parameters to produce Palm wine from toddy sample using Saccharomyces cerevisiae species - Patil, Minal; Ghatage, Abhay; Pathade, Girish (Journal of Neonatal Surgery, 2025)
The study investigated that toddy is popular for the essential tropical alcoholic beverage fermented from the sap collected from coconut trees in the coastal region of Maharashtra. The main species used for this purpose are oil palm (Elaeis guineensis), raffia (Raphia vinifera), coconut (Cocos nucifera) and oil palm (Arenga pinnata). The beverage is fermented by a combination of alcohol, lactic acid and acetic acid. When toddy is fermented, it becomes alcohol, commonly called palm wine. This study aims of providing palm wine by using Saccharomyces cerevisiae isolates focusing on their characteristics, their beneficial role in the industry, especially in relation to palm wine production and products. This toddy or palm wine has many health beneficial properties ,like improvement of Digestion., Boosts Immunity, Heart Health., Bone Health. Energy Boost., Stress Reduction. This study was with aim to produces palm wine from toddy using Saccharomyces cerevisiae isolate